Optimization of bantuan pangan non tunai (BPNT) distribution using bilevel linear programming in siantar martoba subdistrict pematang siantar - Panggabean, Rijen Riston; Sinaga, Lasker Pangarapan (Desimal: Jurnal Matematika, 2024)
Bantuan Pangan Non Tunai (BPNT) is assistance that is in the second decile; in other words, KPMs who are in the first decile will also get assistance. A limited quota of BPNT recipients will result in people in categories such as the elderly group not getting this assistance. This problem arises because there is a significant increase in the population of the elderly group every year. The research method uses secondary data from data sources, namely the social service office, to develop a bilevel model for the problem of distributing food aid on cash by regularizing the bilevel model so that a linear programming model with a single objective function is obtained. In the regularization stage, the gradient descent method is used to find the optimal value of the penalty parameter. From the calculation results of the regularized model, it is found that the values of the variables  x_1= 2956,  x_2= 583, and x_3 = 250 have a value of Z = 3804. This bilevel linear programming model approach provides a strong basis for planning and decision-making related to the distribution of Non-Cash Food Assistance (BPNT) in Siantar Martoba Subdistrict. Therefore, it can be assumed that this bilevel linear programming approach can be used as a guideline for related agencies in allocating resources efficiently.